CNVs in the 22q11.2 Chromosomal Region Should Be an Early Suspect in Infants with Congenital Cardiac Disease. Issue 15 (May 2021) - Pineda, Tatiana; Zarante, Ignacio; Paredes, Angela Camila; Rozo, Juan Pablo; Reyes, Martha C.; Moreno-Niño, Olga María
Background: Congenital heart disease (CHD) is the most common congenital malformation, it is frequently found as an isolated defect, and the etiology is not completely understood. Although most of the cases have multifactorial causes, they can also be secondary to chromosomal abnormalities, monogenic diseases, microduplications or microdeletions, among others. Copy number variations (CNVs) at 22q11.2 are associated with a variety of symptoms including CHD, thymic aplasia, and developmental and behavioral manifestations. We tested CNVs in the 22q11.2 chromosomal region by MLPA in a cohort of Colombian patients with isolated CHD to establish the frequency of these CNVs in the cohort. Methods: CNVs analysis of 22q11.2 by MLPA were performed in 32 patients with apparently isolate CHD during the neonatal period. Participants were enrolled from different hospitals in Bogotá, and they underwent a clinical assessment by a cardiologist and a clinical geneticist. Results: CNVs in the 22q11.2 chromosomal region were found in 7 patients (21.9%). The typical deletion was found in 6 patients (18.75%) and atypical 1.5 Mb duplication was found in 1 patient (3.1%). Conclusions: CNVs in 22q11.2 is a common finding in patients presenting with isolated congenital cardiac disease, therefore these patients should be tested early despite the absence of other clinical manifestations. MLPA is a very useful molecular method and provides an accurate diagnosis.